2021
DOI: 10.56499/jppres20.969_9.3.344
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition of the ethanolic extract from Chromolaena odorata leaves correlates with the cytotoxicity exhibited against colorectal and breast cancer cell lines

Abstract: Context: Colorectal and breast cancer are of particular cellular preventive concern. WIDR cells are an indicator of colorectal cancer development, while HTB and 4T1 cells are involved in breast cancer. The Chromolaena odorata was reported to interfere with the growth of the three cancer cells. Aims: To evaluate the bioactivity of C. odorata against the cytotoxicity of colorectal and breast cancer cells. Methods: Ethanol extract of C. odorata leaves was examined to find chemical compounds by GC-MS, quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Based on a previous study, the anticancer activity of C. odorata was detected from its ethanol extract in a dose-dependent manner [ 23 ]. Similarly, this study showed that treatment with 500 µg/mL EACO selectively decreased the viable cells of MCF-7 and T47D by more than 94% while preserving the Vero cells (61.3%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on a previous study, the anticancer activity of C. odorata was detected from its ethanol extract in a dose-dependent manner [ 23 ]. Similarly, this study showed that treatment with 500 µg/mL EACO selectively decreased the viable cells of MCF-7 and T47D by more than 94% while preserving the Vero cells (61.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Other compounds such as terpenoids (radicol and cadalene), sesquiterpenoids (germacrene D) and phenolic glycosides (citrusin) were found in the aerial parts and the whole plants of C. odorata [ 25 , 28 , 29 , 33 ]. Alpha amyrin, which was previously detected in this plant, is known to inhibit tumor necrosis factor-α (TNF-α), which prevents cancer development [ 23 , 34 ]. The α, β-amyrin is a triterpenoid that functions as an antipyretic, anti-inflammatory, hepatoprotective, and analgesic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C. odorata is easy to find and has potential source of compounds to be used as a co-chemotherapeutic agent. In addition, C. odorata also has anticancer properties with cytotoxicity in cancer cells such as cell cycle arrest, autophagy, and apoptosis (Yusuf, et al, 2021;Olawale, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%